2017
DOI: 10.1242/dev.139683
|View full text |Cite
|
Sign up to set email alerts
|

Towards a CRISPR view of early human development: applications, limitations and ethical concerns of genome editing in human embryos

Abstract: Developmental biologists have become increasingly aware that the wealth of knowledge generated through genetic studies of preimplantation mouse development might not easily be translated to the human embryo. Comparative studies have been fueled by recent technological advances in single-cell analysis, allowing in-depth analysis of the human embryo. This field could shortly gain more momentum as novel genome editing technologies might, for the first time, also allow functional genetic studies in the human embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Recently, it has been employed in several attempts to edit the human embryos (Liang et al, 2015 ; Kang et al, 2016 ; Tang et al, 2017 ). A major technical concern particularly relevant in studies involving human embryos is the potential off-target effects (Callaway, 2016 ; Plaza Reyes and Lanner, 2017 ). Consequently, development of safer genome editing strategy in human embryos is highly anticipated (Cyranoski and Reardon, 2015 ).…”
mentioning
confidence: 99%
“…Recently, it has been employed in several attempts to edit the human embryos (Liang et al, 2015 ; Kang et al, 2016 ; Tang et al, 2017 ). A major technical concern particularly relevant in studies involving human embryos is the potential off-target effects (Callaway, 2016 ; Plaza Reyes and Lanner, 2017 ). Consequently, development of safer genome editing strategy in human embryos is highly anticipated (Cyranoski and Reardon, 2015 ).…”
mentioning
confidence: 99%
“…One major question is whether or not the body’s immune response will accept or reject the foreign genetic elements within the cells. Another important concern is that along with the revolutionary advances of this biotechnology and related sciences, bioethical concerns and legal problems related to this issue are still increasing in view of the possibility of human genetic manipulation and the unsafety of procedures involved [ 49 , 50 , 66 ]. The enforcement of technical and ethical guidelines, and legislations should be considered and need serious attention as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered endonucleases or RNA-guided endonucleases (RGENs) mediated gene targeting has been applied directly in a great number of animal organisms including nematodes and zebrafish [ 20 , 57 ], as well as pigs [ 71 , 85 ]. Since the first permission to use CRISPR/Cas9 in human embryos and in vivo genome editing via homology-independent targeted integration (HITI), an increasing number of studies have identified striking differences between mouse and human pre-implantation development and pluripotency [ 66 ], highlighting the need for focused studies in human embryos. Therefore, more specific criteria and widely accepted standards for clinical research have to be met before human germline editing would be deemed permissible [ 31 ].…”
Section: Applications Of Gene Technologymentioning
confidence: 99%
“…However, laboratories across the globe are now using this technology for innovative approaches in the field of biology. [22] FIG 3 :-Synthego output example with PAM sequence, Guide sequence, and the target region…”
Section: Crispr/cas9 Technologymentioning
confidence: 99%